National Framework for Protecting Australia's Children online indicator reporting - Australian Institue of Health and Welfare (Australian Institute of Health and Welfare (AIHW), 2022)
According to the PDF DownloadNational Framework for Protecting Australia’s Children 2009–2020, all children have the right to have a safe, healthy, and happy childhood. Over 46,500 children and young people aged 0–17 were the subject of child protection substantiation in 2020–21. The National Framework represents a level of collaboration between Australian, State and Territory governments and non-government organisations to protect children. There are two sets of indicators presented within this report that sit under the National Framework; the National Framework indicators and the National Standards indicators.
Keywords: Disadvantage, adversity and resilience; Childhood and child development